The Future of Blood Testing Is the Immunome - Arnaout, Ramy A.; Prak, Eline T. Luning; Schwab, Nicholas; Rubelt, Florian; , the Adaptive Immune Receptor Repertoire Community; Arnaout, Ramy A.; Arora, Rohit; Bashford-Rogers, Rachael; Breden, Felix; Bukhari, Syed Ahmad Chan; Corrie, Brian; Cowell, Lindsay G.; et al. (Frontiers in Immunology, 2021)
It is increasingly clear that an extraordinarily diverse range of clinically important conditions— including infections, vaccinations, autoimmune diseases, transplants, transfusion reactions, aging, and cancers—leave telltale signatures in the millions of V(D)J-rearranged antibody and T cell receptor (TR per the Human Genome Organization [HUGO] nomenclature but more commonly known as TCR) genes collectively expressed by a person’s B cells (antibodies) and T cells We refer to these as the immunome. Because of its diversity and complexity, the immunome provides singular opportunities for advancing personalized medicine by serving as the substrate for a highly multiplexed, near-universal blood test. Here we discuss some of these opportunities, the current state of immunome-based diagnostics, and highlight some of the challenges involved. We conclude with a call to clinicians, researchers, and others to join efforts with the Adaptive Immune Receptor Repertoire Community (AIRR-C) to realize the diagnostic potential of the immunome.